2021
DOI: 10.1038/s41467-021-22829-2
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte-derived microvilli control female fertility by optimizing ovarian follicle selection in mice

Abstract: Crosstalk between oocytes and surrounding somatic cells is crucial for mammalian oogenesis, but the structural mechanisms on oocytes to control female reproduction remain unknown. Here we combine endogenous-fluorescent tracing mouse models with a high-resolution live-cell imaging system to characterize oocyte-derived mushroom-like microvilli (Oo-Mvi), which mediate germ-somatic communication in mice. We perform 3D live-cell imaging to show that Oo-Mvi exhibit cellular characteristics that fit an exocrine funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…Cumulus cells utilize transzonal projections (TZPs) and gap junctions to transfer molecular cargoes that are critical for regulating the process of oocyte maturation (Clarke, 2018). Conversely, oocytes use structures named oocyte‐derived mushroom‐like microvilli (Y. Zhang et al, 2021) and paracrine signaling to regulate much of the flow of ions and molecules toward the cumulus (Li & Albertini, 2013). In the past few years, a less well‐characterized and new potential mechanism has been identified that involves the exosomal transfer of noncoding RNAs from cumulus to oocytes (De Ávila et al, 2020; Russell et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Cumulus cells utilize transzonal projections (TZPs) and gap junctions to transfer molecular cargoes that are critical for regulating the process of oocyte maturation (Clarke, 2018). Conversely, oocytes use structures named oocyte‐derived mushroom‐like microvilli (Y. Zhang et al, 2021) and paracrine signaling to regulate much of the flow of ions and molecules toward the cumulus (Li & Albertini, 2013). In the past few years, a less well‐characterized and new potential mechanism has been identified that involves the exosomal transfer of noncoding RNAs from cumulus to oocytes (De Ávila et al, 2020; Russell et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…According to the analysis of the dynamic metabolome profiles in oocytes during in vivo maturation, lipid and fatty acid metabolism played a vital role in oocyte meiotic process ( 5 ). Additionally, the bi-directional interaction between oocyte and granulosa cells has long been proved to play a key role in oocyte growth and maturation ( 4 , 33 ), indicating the possible correlation between granulosa cells metabolic status and oocyte maturation, which is less investigated in previous studies. In the present study, we compared the transcriptome of granulosa cells from healthy women and women with PCOS, and found that metabolic process and ovarian steroidogenesis were significantly impaired in PCOS granulosa cells through GO and KEGG pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that loss of gap junctions causes disruption of bidirectional communication between oocytes and follicle cells and results in infertility. Related to this is the recent report that interference with formation of oocyte microvilli by deletion of radixin, the microvilli-forming gene, leads to retardation of both oocyte growth and follicle development and to reduced fertility in mice ( Zhang et al, 2021 ).…”
Section: Oocyte–follicle Cell Communication In the Ovarymentioning
confidence: 99%